Triple Hit Lymphoma: Rare Cases With Less Dire Than Usual Prognosis. (December 2016) - Kallen, Michael E.; Alexanian, Serge; Said, Jonathan; Quintero-Rivera, Fabiola
Triple hit lymphomas are a subset of so-called double hit non-Hodgkin lymphomas exhibiting simultaneous gene translocations/disruption of MYC, BCL2, and BCL6 ; however, their overlapping morphologic features and complex genetic rearrangements can render classification and prognostication vexing. Clinically triple hit lymphomas are thought to demonstrate aggressive behavior, similar to or worse than that of double hit lymphomas. Only rare reports of long term survivors exist and raise the possibility that unidentified morphologic, immunologic, or cytogenetic differences may impart a less adverse prognosis than current literature and opinion may suggest. Here we report 3 such cases with less aggressive behavior. Cases such as these may prove useful in comparing outcomes, and underlying mechanisms of tumor progression, in aggressive non-Hodgkin lymphomas.